Structural Characteristics and Immunomodulatory Effects of a Long-Chain Polysaccharide From Laminaria japonica - Cui, Jiamei; Wang, Yunpeng; Kim, Eunyoung; Zhang, Chongyu; Zhang, Guiguo; Lee, Yunkyoung (Frontiers in Nutrition, 2022)
Polysaccharides derived from Laminaria japonica (LJPS) have shown a variety of beneficial effects on improving human health; however, the structural features and bioactivities of long-chain LJPS remain unclear. This study aimed to investigate the structural characteristics and bioactivities of a novel long-chain LJPS. Results showed that the LJPS was composed of Fuc, Rha, Ara, Gal, Glc, Xyl, Man, Fru, Rib, GalA, GluA, GlcA, and ManA, with a molar ratio of 35.71:1.48:0.28:13.16:0.55:2.97:6.92:0.58:0.41:0.14:3.16:15.84:18.79. Of these, Fuc, Gal, Man, GlcA, and ManA were the predominant components with an accumulated proportion of 93.6%. The LJPS was found to consist of seven types of the monomer residues, and the main interchain glycosidic linkages were β -D-(1 → 2), α -D-(1 → 3), (1 → 4), and (1 → 6), and the molecular mass was 5.79 × 104 g/mol. Regarding the molecular conformation, LJPS was a multi-branched, long-chain macromolecule, and appeared in a denser crosslinking network with highly branched and helix domains in the terms of morphology. Additionally, the LJPS had no toxicity to mouse macrophage cells and exhibited biphasic immuno-modulating capacity. The present findings suggested that the long-chain LJPS might be an attractive candidate as an immunopotentiating and anti-inflammatory functional food, and this study also provides a feasible approach to decipher the structural characteristics and spatial conformations of plant-derived polysaccharides.